2005
DOI: 10.1037/0893-3200.19.4.643
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of antisocial behavior in older male siblings for younger brothers and sisters.

Abstract: The contribution of younger male and female siblings' conflict and involvement in deviant activities with their older brothers to younger siblings' adolescent adjustment problems was examined in the context of parenting. Ineffective parenting during younger siblings' childhood had no direct effects on adjustment but facilitated their exposure to older brothers' deviant peers and activities. The effect of sibling conflict on adjustment was mediated by younger siblings' coparticipation in deviant activities with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
117
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(132 citation statements)
references
References 25 publications
11
117
0
4
Order By: Relevance
“…These studies are typically restricted to twochild families or, in larger families, the effects of other siblings are ignored. Moreover, it is common to focus only on the effect of an older sibling on a younger child and to allow only for cross-sectional associations between sibling outcomes (Slomkowski, Rende, Conger, Simons, & Conger, 2001;Snyder, Bank, & Burraston, 2005). Where reciprocal relationships are considered, some form of cross-lagged model is generally employed with the outcome of one child at time t (or the change in their outcome between t -1 and t) depending on their sibling's outcome at time t -1 (e.g.…”
Section: Bivariate Autoregressive Cross-lagged Modelsmentioning
confidence: 99%
“…These studies are typically restricted to twochild families or, in larger families, the effects of other siblings are ignored. Moreover, it is common to focus only on the effect of an older sibling on a younger child and to allow only for cross-sectional associations between sibling outcomes (Slomkowski, Rende, Conger, Simons, & Conger, 2001;Snyder, Bank, & Burraston, 2005). Where reciprocal relationships are considered, some form of cross-lagged model is generally employed with the outcome of one child at time t (or the change in their outcome between t -1 and t) depending on their sibling's outcome at time t -1 (e.g.…”
Section: Bivariate Autoregressive Cross-lagged Modelsmentioning
confidence: 99%
“…Although the authors examined a directional model of sibling influence going from older to younger, they suggest that coercive and conflictual family interactions are a systemic social process that affects all family members rather than solely being unidirectional. In a similar vein, Snyder et al [43] report that these predictors were synergistically associated with increased risk for younger brothers' and sisters' maladjustment and antisocial behaviors. Their findings also suggest that early sibling conflict may be predictive of conflictual and aggressive interpersonal relations, especially when sibling conflict is paired with ineffective parenting strategies [29] however; this association was not tested directly.…”
Section: Consequences Of Parental and Sibling Conflictmentioning
confidence: 88%
“…Youths' imitation of their parents has been demonstrated in a number of domains, including teenage alcohol consumption [36], adult intimate relationships [37], as well as anxiety and anxiety-maintaining behaviors (i.e., escape and avoidance; [38,39]. Imitation has also been shown between siblings, such as in the areas of risky sexual behavior and teen pregnancy [27,40], substance use [26,41], as well as delinquent and antisocial behaviors [42,43], while other prosocial behaviors such as empathy [21] and behavioral control [44] can also be learned via siblings. These studies illustrate the impact of social learning within the family and are consistent with Bandura's theory.…”
Section: Social Learning Theorymentioning
confidence: 99%
“…Deviance and delinquency have traditionally been defined in social science literature as behaviors that compromise the well-being of others (Bennett and Robinson, 2000). The connection between sibling relationships and deviance may be due to several factors: The observation of deviant behavior in a sibling, exposure to behavior that promotes and encourages deviancy, such as positive attitudes and encouragement to participate in delinquent behavior (Snyder et al, 2005) and pre-existing conflict in the sibling relationship Pike et al, 2005). Genetic research has found that the influence of siblings on risky behavior is often outweighted by social factors instead of pre-determined genetic factors (McGue et al, 1996;Natsuaki et al, 2009).…”
Section: Introductionmentioning
confidence: 99%